Pertumbuhan dan Produksi Jagung Manis terhadap Kombinasi Pop Ayam dengan Kambing dan POC dari Air Cucian Beras - Hasibuan, Nur Hidayah; Harahap, Ariani Syahfitri; Luta, Devi Andriani; Adji Syahputra, Bambang Surya (UNIVERSITAS LABUHANBATU, 2024)
The purpose of this study was to determine the interaction of the combination of POP from chickens and goats and POC from rice water on the growth of sweet corn plants. The study used a completely randomized block design (RAK), then a statistical test of variance analysis was carried out on each observation which was measured for its truth using Duncan's multiple range test. Based on the results of the research and discussion, it can be concluded that from the data from the analysis of variance, the combination of interactions between chickens and goats gives significantly different interaction effects on the growth of plant height (cm), leaf area (cm2), number of leaves (strands), number of rows of cobs. , cob diameter (cm2), weight per sample (g), and weight per plot (kg). The combination of chicken pop with goat gave a significantly different effect to the 75% chicken + 25% goat treatment. Giving POC of rice washing water had a real effect on the treatment of 750ml/l water Keywords: sweet corn, chicken pop, goat pop, rice washing water poc